Chapter The economic and environmental impact of large ships on the territory, on the coast and on the sea: the MSC cruises case study - Candura, Anna Rosa (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Cruise tourism is expanding everywhere, despite the pandemic; CLIA (2021) reports that, in 2020, the economic damage was around 77 billion dollars, but records a significant increase in travelers who aspire to join a cruise. Cruise ships and their economic impact have been the subject of research for many years and the data, which can be obtained from various sources, denote the importance of this particular sector. Through the MSC case study, this contribution aims to partecipate in the reflection on the theme of sustainability, to look at the possibility of directing cruise tourism towards a new way of introducing Man into the landscape.